Effect of Febrile Seizures on Oxidant Status - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Erythrocyte malondialdehyde (EMA), glutathione peroxidase (GPO), and superoxide dismutase (SDM) levels were assessed in 31 children with a febrile seizure and 30 without, in a study at Dokuz Eylul University, Izmir, Turkey.